รูปแบบการขับเคลื่อนนโยบายสาธารณะแบบมีส่วนร่วมของชุมชน กรณีศึกษาการจัดการขยะอินทรีย์ของชุมชน ตำบลศิลา อำเภอเมือง จังหวัดขอนแก่น : A Model of Participatory Public Policy Mobilization for Community Organic Waste Management: A Case Study of Sila Subdistrict, Khon Kaen Province - นาคำ มานะ; นาคำ พะเยาว์ (Journal of Humanities and Social Sciences (HUSOKKU), 2026)
This article aimed to examine the problems associated with organic waste management and the participatory public policy mobilization process for organic waste management in Sila Municipality, Mueang District, Khon Kaen Province.The study employed Participatory Action Research (PAR) to investigate the model, mechanisms, and processes of participatory public policy mobilization in community-based organic waste management. Data were collected from municipal administrators and officers, community leaders, households practicing waste segregation, waste collectors, and users of organic waste products in seven pilot communities. The findings revealed that the decentralization of authority and resources from the municipality to local communities enabled community members to participate in designing operational systems and developing flexible management mechanisms suited to local contexts. This process contributed to the emergence of “green households” practicing waste segregation, as well as volunteer groups collecting organic waste for the production of compost and bio-fermented liquids for agricultural use. Such practices were consistent with the socio-economic context of peri-urban communities where agriculture remains a primary occupation. Consequently, the volume of waste requiring municipal disposal was significantly reduced. Municipal officers and the research team continuously supported community organic waste management through knowledge enhancement on waste management practices, monitoring meetings, household visits, visits to agricultural plots utilizing organic waste products, lesson-learned sessions, and community feedback activities. These processes strengthened community confidence and fostered the effective mobilization of participatory public policy in organic waste management.